Mawah Practices in Aceh: Syariah Legitimacy Based on Fatwas and Islamic Jurisprudence - Maksalmina Maksalmina (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
This study aims to identify mawah practices in Acehnese society and analyze their legitimacy based on the Ulama Consultative Council’s fatwas and Islamic jurisprudence. This research employs a field research design with a normative approach, focusing on four districts in Pidie Regency. Data were collected through observations and interviews with landowners and cultivators and analyzed using the Miles and Huberman model. The analysis is grounded in relevant Islamic jurisprudential principles, such as qiyas (muzara’ah to mudharabah) and the rule of al-ashlu fi al-muamalat al-ibahah hatta yadulla ad-dalilu ala khilafihi. The findings show that mawah umong (rice fields) is a collaborative contract between landowners (malik) and cultivators, where profit-sharing agreements are based on the harvest yield, the land’s condition, and its location. Mawah umong is categorized into five types: mawah pajoh asoe, mawah bulueng dua, mawah bulueng lhee, mawah bulueng peut, and mawah bulueng limeng. The study confirms that most mawah practices fulfill the requirements of Shariah contracts and align with Islamic jurisprudence. Academically, this research contributes by validating mawah practices as legitimate cooperative mechanisms rooted in traditional Acehnese customs while providing a framework for their evaluation based on Islamic principles.Keywords: Mawah Practices, Ulama Consultative Council’s Fatwa, Pidie Regency